Manajemen Peningkatan Kemandirian Siswa SLB C Budi Asih Wonosobo - Susiyani, Ucik (Media Manajemen Pendidikan, 2024)
This research is research on children with special needs at SLB C Budi Asih Wonosobo which aims to 1) analyze the management of increasing student independence, 2) explain the supporting and inhibiting factors for implementing management to increase student independence, and 3) analyze the level of student independence. The research method uses a phenomenological approach with a qualitative descriptive design. The data in this research was obtained through interviews, observation and documentation. Interviews were conducted with school principals, teachers, supervisors, school committees and also students' parents, while observations and documentation were carried out directly in the field. Data analysis in this research uses data triangulation, both using source triangulation and also technical triangulation. Based on the results of data analysis, the conclusions obtained are: 1) SLB C Budi Asih Wonosobo has carried out 4 management functions (planning, organizing, implementing and controlling) well; 2) Supporting factors in the program to increase student independence are parents who are proactive in their children's progress, competent teachers, and supporting facilities, while inhibiting factors are the condition of each student's disability, parents who do not follow instructions from the school, and limited physical facilities, especially the availability of study room; and 3) students' independence is appropriate to their mental age.